Functional, oncological, regret and complications following partial gland cryo-ablation for low-risk prostate cancer associated with MPMRI targets - Lepor, Herbert; Cao, Thomas; Tafa, Majlinda; Wysock, James S. (Urologic oncology, 2025)
•50% of men on AS undergo whole gland treatment (WGT).•2% of men with GGG1 and MRI target following focal cryo underwent WGT at 5 years.•No men undergoing focal cryo ever developed incontinence.•No men undergoing focal cryo reported treatment related regret.•Focal cryo should be considered for GGG1 associated with an MRI target. There is increasing interest in ablative focal therapy (AFT) for treating clinically localized prostate cancer. The objective of the present study is to report treatment related complications and regret, functional and oncological outcomes of primary partial gland cryo-ablation (PPGCA) for men with low-risk prostate cancer associated with a multiparametric Magnetic Resonance Imaging (mpMRI) target. The present analysis includes 54 subjects enrolled in an Institutional Review Board (IRB) approved outcomes registry with low-risk prostate cancer undergoing PPGCA whose disease was associated with an MRI target. The surveillance protocol included mpMRI at 6 months, 2, 3.5, and 5 years, and surveillance prostate biopsies. Clinically significant prostate cancer (csPCa) recurrence was defined as any biopsy core with Gleason pattern (GP4). Freedom-from-failure (FFF) included men who: did not experience prostate cancer mortality, develop metastasis or undergo whole gland salvage treatment (WGST). All men underwent at least 1 post-treatment biopsy. The International Prostate Symptom Score (IPSS), Sexual Health Inventory for Men (SHIM) and Treatment Related Regret (TRR) surveys were self-administered at 1 year. There were no day-of-surgery or 30-day postoperative hospital admissions. There were no rectal injuries or other technical complications. The 5-year freedom from csPCa recurrence and FFF was 84% and 96%, respectively. At 1 year, only 1 man used a protective pad and no men expressed significant TRR. Overall, the mean decreases in IPSS and SHIM scores between baseline and 1-year was 3.4 (34.7%) and 3.7 (20.4%), respectively. Erectile function was preserved in 72% of men by 1 year. The favorable oncological outcomes, absence of treatment related complications, Treatment Related Regret (TRR), urinary incontinence, rectal injury, improvement in lower urinary tract symptoms (LUTS), and modest changes in sexual function suggests PPGCA should be considered an option for managing selected cases of low-risk prostate cancer associated with an MRI target.